2013
DOI: 10.3892/or.2013.2502
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of testin and survivin in breast cancer subtypes

Abstract: Abstract. Testin (TES) is a putative tumour-suppressor gene downregulated in various types of cancers. Survivin is a nodal protein involved in multiple signalling pathways, tumour maintenance and inhibition of apoptosis. Previous studies indicate that TES and survivin can functionally interact and modulate cell death and proliferation in breast cancer cells. The aim of the present study was to investigate the expression and prognostic relevance of TES and survivin in breast cancer subtypes examining a large co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(60 reference statements)
3
12
1
Order By: Relevance
“…Specifically, APOP drugs YM155, bortezomib, and carfilzomib displayed most potent anticancer activity as single agents across all TNBC lines, as indicated by higher AUC (red color) in Figure 3A. YM155 is a selective suppressant of survivin, a member of the inhibitor of antiapoptosis (IAP) family that has higher nuclear activity in TNBC compared to other subtypes (17). Interestingly, MDA-MB-231 TNBC cells were more sensitive to YM155 induced growth inhibition than SKBR3 or MCF7 non-TNBC cell lines (18).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, APOP drugs YM155, bortezomib, and carfilzomib displayed most potent anticancer activity as single agents across all TNBC lines, as indicated by higher AUC (red color) in Figure 3A. YM155 is a selective suppressant of survivin, a member of the inhibitor of antiapoptosis (IAP) family that has higher nuclear activity in TNBC compared to other subtypes (17). Interestingly, MDA-MB-231 TNBC cells were more sensitive to YM155 induced growth inhibition than SKBR3 or MCF7 non-TNBC cell lines (18).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that Testin inhibited the growth of breast and uterine as well as ovarian cancer cell proliferation through caspase-dependent and caspase-independent apoptosis (18,19). Downregulation of Testin has been reported to have a significant association with highly aggressive breast tumor subtypes, such as triple-negative and luminal B tumors, along with the prognostic relevance of nuclear expression of survivin (30). Weeks et al discovered that 100% of the ALL samples (n=20) were methylated at the Testin promoter, whereas the matched remission (n=5), normal bone marrow (n=6) and normal PBL (n=5) samples were unmethylated.…”
Section: Discussionmentioning
confidence: 99%
“…There are three isoforms of human Testin, which differ in the size of the 3'-UTR encoded by exon 7 (11)(12)(13). Testin mRNA is expressed in all normal human tissues, while low or lack of Testin expression has been found in prostate cancer, glioblastoma, endometrial carcinoma, ovarian, breast, uterine, colon cancer, esophageal and gastric cancer, acute myelogenous and acute lymphoblastic leukemia (ALL) and nasopharyngeal carcinoma (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Tatarelli et al observed lack of expression in 22% of cancer cell lines and in 44% of the cell lines derived from hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the methylation status of the TES gene, which has the potential to be used in routine clinical setting as a biomarker for astrocytomas of different malignancy grade, was analysed. Previous data have suggested the possibility that down-regulation of TES is associated with alterations in cell adhesion and motility, and therefore, may lead to the development of tumours with an aggressive phenotype (6). The TES gene was noticed to be highly methylated in glioblastomas (5,10,15), and the tumour-associated methylation of TES was confirmed in cultured glioblastomas and glioblastoma cell lines (10).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of hypermethylation of CpG dinucleotides varies significantly between different malignancy grades of gliomas (5). Previous data in breast cancer suggest the possibility that down-regulation of testin (TES) is associated with alterations in cell adhesion and motility, and therefore may lead to the development of tumours with an aggressive phenotype (6). …”
Section: Introductionmentioning
confidence: 99%